Utilization and Implementation of the Digital Bukukas Application for MSMEs - Iin Muyasarah; Nur Habibah; Hu’shila Awalia Rizqiani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This community service aims to able to provide information related to the impertanve of recording financial transactions in every business run by UMKM. Recording financial transactions can be done by utilizing the digital technology of the Bukukas recording application. The Bukukas application can make it easier for UMKM to record transactiond in their business. The method used in this activity is socialization and practice of using Bukukas by presenting UMKM in Sekumpul Ujung Martapura. It was held at the RT 11 residence and was attended by 20 different types of UMKM. The results of the implementation of community service, the introduction and practice of using the Bukukas digital recording application can be reparacticed by UMKM. This service activity was attended by 20 UMKM with variouse types pf UMKM and the there were only 3 UMKM that had difficulty using the Bukukas application. The diffeculties experienced by the 3 UMKM are due to the application of the systematics of carrying out buying and selling activities where the buying and selling is carried out quickly.